Improving the Integrity of a Voting Process with Biometric Authentication and Data Encryption - Walter M. Molina; Lino R. Mac Kay; Daniel Subauste (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Throughout the years, the voting process has under-gone a digital transformation, aiming to achieve greater control and optimize time while ensuring the integrity of each vote. While previous solutions have introduced changes in architecture and security processes, there hasn't been a defined secure model for voting. The applications developed in this study employed biometrics and a fingerprint reader for authentication security, along with cryptography algorithms to safeguard the flow of voting data. Experts and individuals involved in the Peruvian electoral process evaluated the web and mobile applications to determine their viability in a real-world context and their potential to enhance the electoral process in Peru. This evaluation was conducted through a case study involving 50 participants and satisfaction surveys, which qualitatively assessed the usability and effectiveness of the applications. The results indicated that the developed applications were well-received, perceived as intuitive, and provided an interactive experience.